2016
DOI: 10.1016/j.shaw.2016.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and Fatigue Among Seafarers: The Role of Environmental Stressors, Duration at Sea and Psychological Capital

Abstract: BackgroundSeafaring is an inherently stressful environment. Because working time and leisure time is spent in the same confined environment for a prolonged period of time, many stressors present in seafaring can also be conceived of as chronic. We explored the effects of duration at sea, seafaring experience, environmental stressors, and psychological capital (PsyCap) on the sleep quality and fatigue of seafarers. PsyCap is a construct that draws upon ideas from positive psychology and positive organizational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(85 citation statements)
references
References 29 publications
(38 reference statements)
5
60
0
3
Order By: Relevance
“…PsyCap and its four components may be key to better understand the variation in stress, as well as intentions to negative behaviors (28). Previous studies have showed the a negative relation between PsyCap and fatigue in a variety of professions (27,29). Analogously, Kim and Jang reported that seafarers' self-efficacy will have a negative effect on fatigue (30).…”
Section: Introductionmentioning
confidence: 98%
“…PsyCap and its four components may be key to better understand the variation in stress, as well as intentions to negative behaviors (28). Previous studies have showed the a negative relation between PsyCap and fatigue in a variety of professions (27,29). Analogously, Kim and Jang reported that seafarers' self-efficacy will have a negative effect on fatigue (30).…”
Section: Introductionmentioning
confidence: 98%
“…Seafarer is considered to be a highly stressful [1] and high-risk occupation in terms of physical and mental exhaustion [2,3]. In fact, seafarers are easily subject to many psychosocial stressors and physical stressors, encompassing high leadership responsibilities (time pressure and decision-related pressure, under-qualified subordinate crew members), separation from family, loneliness, cross-cultural communication, fatigue and sleep deprivation, physical need, recreation scarcity, workplace noise, ship movement, vibration and heat [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…This difference might be due to variations in the work system characteristics between these two ship crews. Compared to a tugboat, a oating crane likely stays in one place for a more extended period because of its work nature, and no chance of getting off the ship to ward off boredom induces a more monotonous working rhythm in ship crews [15]. Whereas on a tugboat, although the entire sailing time may be longer, in conditions where the ship has to wait for loading and unloading, the crew may get off the boat to shop for food and needs on board or to banish boredom.…”
Section: Discussionmentioning
confidence: 99%
“…Fatigue is experienced commonly among the general working population every day, with the estimated prevalence being as high as 22% [2]. Working at sea certainly makes one susceptible to fatigue; therefore, the shipping industry is increasingly concerned about the possible effects of fatigue on personal and operational safety and the general health and wellbeing of workers [2,3]. Maritime incidence analyses have shown that approximately 80% of maritime casualties are due to human error [4] and 26% of shipping incidents are associated with fatigue in seafarers [5].…”
Section: Introductionmentioning
confidence: 99%